2009
DOI: 10.1128/jb.01410-08
|View full text |Cite
|
Sign up to set email alerts
|

Similar and Divergent Effects of ppGpp and DksA Deficiencies on Transcription in Escherichia coli

Abstract: The concerted action of ppGpp and DksA in transcription has been widely documented. In disparity with this model, phenotypic studies showed that ppGpp and DksA might also have independent and opposing roles in gene expression in Escherichia coli. In this study we used a transcriptomic approach to compare the global transcriptional patterns of gene expression in strains deficient in ppGpp (ppGpp 0 ) and/or DksA (⌬dksA). Approximately 6 and 7% of all genes were significantly affected by more than twofold in ppGp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
143
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(155 citation statements)
references
References 55 publications
11
143
1
Order By: Relevance
“…The iraD gene was not found among this set but may have been missed because of growth condition differences or due to difficulty in the detection of the iraD transcript. The mechanism of this antagonistic and (p)ppGpp-independent effect by DksA on some genes appears to be competition with the GreA/B elongation factors (1,2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The iraD gene was not found among this set but may have been missed because of growth condition differences or due to difficulty in the detection of the iraD transcript. The mechanism of this antagonistic and (p)ppGpp-independent effect by DksA on some genes appears to be competition with the GreA/B elongation factors (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…However, DksA has effects on phenotypes such as adhesion, motility and chemotaxis in relA spoT double mutant strains [so-called "(p)ppGpp 0" strains] unable to synthesize (p)ppGpp (1,28), suggesting that DksA can function independently of (p)ppGpp. Microarray and fusion experiments indicated that DksA and (p)ppGpp have opposing effects on a subset of genes primarily involved in fimbriae regulation, chemotaxis and motility (1,2).…”
mentioning
confidence: 99%
“…However, recent studies of UPEC and E. coli K-12 have challenged the previously ascribed role of DksA during ppGpp-dependent transcriptional regulation (1,3,125). DksA not only regulates motility and cell-to-cell adhesion independently of ppGpp but also controls bacterial adherence oppositely of ppGpp (125).…”
Section: Uropathogenic Escherichia Colimentioning
confidence: 99%
“…Data from phenotypic studies indicate that the overproduction of DksA by ppGpp 0 bacteria can compensate for the lack of the alarmone (160). Additionally, ppGpp and DksA have opposite effects on certain E. coli traits and promoters (1,125). Furthermore, in vitro assays show opposite and independent regulations of some promoters by these two stringent response components (123,131).…”
Section: Regulatory Targets Of Ppgppmentioning
confidence: 99%
“…Some of the regulatory actions of ppGpp on the activity of RNA polymerase are achieved in conjunction with DksA, a protein with structural homology to Gre transcription factors (22). However, independent and opposing roles for DksA have also been observed, supporting unique functions for DksA (23,24). DksA has been shown to play a role in the virulence of several pathogens including Salmonella; however, it is still unclear how adjustments in gene expression by DksA contribute to Salmonella pathogenesis (25).…”
mentioning
confidence: 99%